Penggunaan Giongo dalam Webtoon Ikemen Sugite - Diana Rizki Oktarina (Program Studi Sastra Jepang, Universitas Komputer Indonesia Bandung, 2019)
Abstract : The aim of this study is to understand the use of one part of the Japanese onomatopoeia, namely giongo consisting of giseigo, a word that shows the sounds of living things, and giongo, a word that shows the sound of inanimate objects, which is found in 15 chapters of Webtoon’s Ikemen Sugite (Nayameru Otoko no Nichijyou). By using pragmatic studies, especially in the context of the use of words, it can be seen that the results of this study indicate that there are 10 words included in giseigo, and 10 words included in giongo. The high frequency of using giongo in this webtoon shows that giongo is one type of onomatopoeia that is widely used in Japanese, is also a word that represents the emotions of speakers in a written work or conversation so that it is necessary to learn by Japanese learners. Keywords: Onomatopoeia, Giongo, Giseigo Vocabulary, Webtoon Abstrak : Tujuan penelitian ini adalah untuk mengetahui salah satu bagian dari onomatope Bahasa Jepang, yaitu giongo, yang terdiri dari giseigo, kata yang menunjukkan suara makhluk hidup, dan giongo, kata yang menunjukkan benda mati, yang terdapat dalam 15 chapter Webtoon Ikemen Suite (Nayameru Otoko No Nichijyou). Penelitian ini menggunakan kajian pragmatik, khususnya konteks penggunaan kata, dan berdasarkan analisis yang telah dilakukan terdapat 10 kata giseigo, dan 10 kata giongo. Tingginya frekuensi penggunaan giongo dalam webtoon ini menunjukkan bahwa giongo adalah salah satu onomatope yang banyak digunakan dalam bahasa Jepang, dan juga merupakan kata yang mewakili emosi penutur dalam karya tulis ataupun percakapan sehingga perlu dipelajari oleh pembelajar bahasa Jepang. Kata Kunci: Onomatope, Giongo, Giseigo, Kosa kata, Webtoon